For $a\in R,$ $\left| a \right|>1$ let $\displaystyle \lim_{n \to \infty}\dfrac{1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n}}{{{n}^{\dfrac{7}{3}}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}=54$ , then possible value(s) of a is(are)
(a)8
(b)-9
(c)7
(d)-6
Answer
Verified
123k+ views
Hint: To solve this question, firstly we will simplify the function in terms of which limit is to be applied and make it more simpler so that we can use the concept of limit as summation. After that we will get two integrals in numerator and denominator, we will solve them and then putting values back to fraction, we will fraction equal to 54 and solve the quadratic equation obtained to get values of a.
Complete step-by-step answer:
Let us see what the concept of limit as summation is.
Suppose we have to evaluate a limit question, say $\displaystyle \lim_{n \to \infty}f(n)$, if we can transform this limit into the form $\displaystyle \lim_{n \to \infty}\dfrac{1}{n}\sum\limits_{r=a}^{b}{f\left( \dfrac{r}{n} \right)}$, then $\displaystyle \lim_{n \to \infty}f(n)=\int\limits_{a}^{b}{f(x).dx}$.
Now, first let us simplify the value on which we have to apply the limit.
So, we have $\dfrac{1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n}}{{{n}^{\dfrac{7}{3}}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$.
Now, let us take \[{{n}^{\dfrac{1}{3}}}\] from denominator to numerator, which will give us \[{{n}^{-\dfrac{1}{3}}}\] in numerator.
So, we have $\dfrac{{{n}^{-\dfrac{1}{3}}}\left( 1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n} \right)}{{{n}^{2}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$
Or, $\dfrac{\sqrt[3]{\dfrac{1}{n}}\left( 1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n} \right)}{{{n}^{2}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$
Multiplying, $\sqrt[3]{\dfrac{1}{n}}$ with terms in bracket, we get
$\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{{{n}^{2}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$
Multiplying, $\sqrt[3]{\dfrac{1}{n}}$ with terms in bracket in denominator, we get
$\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{\left( \dfrac{{{n}^{2}}}{{{(na+1)}^{2}}}+\dfrac{{{n}^{2}}}{{{(na+2)}^{2}}}+.....+\dfrac{{{n}^{2}}}{{{(na+n)}^{2}}} \right)}$
Now, in denominator, multiplying denominator and numerator of each terms by $\dfrac{1}{{{n}^{2}}}$, we have
$\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{\left( \dfrac{1}{{{\left( a+\dfrac{1}{n} \right)}^{2}}}+\dfrac{1}{{{\left( a+\dfrac{2}{n} \right)}^{2}}}+.....+\dfrac{1}{{{\left( a+\dfrac{n}{n} \right)}^{2}}} \right)}$
On observing patterns in numerator and denominator, we can write the terms collectively in terms of summation.
So, we can write numerator $\sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}}$ as \[\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}\] and,
Denominator $\dfrac{1}{{{\left( a+\dfrac{1}{n} \right)}^{2}}}+\dfrac{1}{{{\left( a+\dfrac{2}{n} \right)}^{2}}}+.....+\dfrac{1}{{{\left( a+\dfrac{n}{n} \right)}^{2}}}$ as $\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}$.
So, we have whole fraction $\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{\left( \dfrac{1}{{{\left( a+\dfrac{1}{n} \right)}^{2}}}+\dfrac{1}{{{\left( a+\dfrac{2}{n} \right)}^{2}}}+.....+\dfrac{1}{{{\left( a+\dfrac{n}{n} \right)}^{2}}} \right)}$ as $\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$.
So, $\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$
Now, let $\dfrac{r}{n}=x$
Here r is variable and n is constant
So, differentiating $\dfrac{r}{n}=x$ both side with respect to x, we get
$\dfrac{dr}{n}=dx$
Putting limit in $\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$, we have
$\displaystyle \lim_{n \to \infty}\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$
Now, value of $\dfrac{r}{n}=x$, at r = 1 and $n\to \infty $, we have x = 0 as $\dfrac{1}{\infty }\to 0$ and value of $\dfrac{r}{n}=x$, at r = n and $n\to \infty $, we have x = 1.
So, we can rewrite $\displaystyle \lim_{n \to \infty}\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$ as \[\dfrac{\int\limits_{0}^{1}{\sqrt[3]{x}}dx}{\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}dx}\].
So, let ${{I}_{1}}=\int\limits_{0}^{1}{\sqrt[3]{x}}$ and ${{I}_{2}}=\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}$
We know that \[\int\limits_{a}^{b}{f(x)}=F(b)-F(a)\] and \[\int\limits_{{}}^{{}}{{{x}^{n}}.dx=\dfrac{{{x}^{n+1}}}{n+1}}+C\]
So, ${{I}_{1}}=\int\limits_{0}^{1}{\sqrt[3]{x}}$
${{I}_{1}}=\left( \dfrac{3}{4}{{x}^{\dfrac{4}{3}}} \right)_{0}^{1}$
${{I}_{1}}=\dfrac{3}{4}\left( 1-0 \right)$
So, ${{I}_{1}}=\dfrac{3}{4}$
Now, ${{I}_{2}}=\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}$
Let, a + x = t
At, x = 0, t = a and at x = 1, t = a + 1
Differentiating both sides, we get
dx = dt
so, ${{I}_{2}}=\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}$ is transformed to ${{I}_{2}}=\int\limits_{a}^{a+1}{\dfrac{1}{{{\left( t \right)}^{2}}}}dt$
${{I}_{2}}=\left( -\dfrac{1}{t} \right)_{a}^{a+1}$
${{I}_{2}}=\left( \dfrac{1}{a}-\dfrac{1}{a+1} \right)$
Putting back value of both integral in \[\dfrac{\int\limits_{0}^{1}{\sqrt[3]{x}}dx}{\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}dx}=54\],
We get, \[\dfrac{\dfrac{3}{4}}{\left( \dfrac{1}{a}-\dfrac{1}{a+1} \right)}=54\]
On simplifying, we get
\[\dfrac{1}{72}=\left( \dfrac{1}{a}-\dfrac{1}{a+1} \right)\]
On solving, we get
${{a}^{2}}+a-72=0$
On factorising, we get
${{a}^{2}}+9a-8a-72=0$
On simplifying, we get
( a + 9 )( a – 8 ) = 0
Or, a = -9, 8
So, the correct answers are “Option a and b”.
Note: To solve such a question must know the concept of limit as summation and also, one should not put limit directly as it will give nothing so one must proceed ahead by simplifying the brackets and then use limit as summation to easily simplify the question. Always remember that \[\int\limits_{a}^{b}{f(x)}=F(b)-F(a)\] and \[\int\limits_{{}}^{{}}{{{x}^{n}}.dx=\dfrac{{{x}^{n+1}}}{n+1}}+C\] Try not to make any calculation error as this will make question more complex and hard to solve.
Complete step-by-step answer:
Let us see what the concept of limit as summation is.
Suppose we have to evaluate a limit question, say $\displaystyle \lim_{n \to \infty}f(n)$, if we can transform this limit into the form $\displaystyle \lim_{n \to \infty}\dfrac{1}{n}\sum\limits_{r=a}^{b}{f\left( \dfrac{r}{n} \right)}$, then $\displaystyle \lim_{n \to \infty}f(n)=\int\limits_{a}^{b}{f(x).dx}$.
Now, first let us simplify the value on which we have to apply the limit.
So, we have $\dfrac{1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n}}{{{n}^{\dfrac{7}{3}}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$.
Now, let us take \[{{n}^{\dfrac{1}{3}}}\] from denominator to numerator, which will give us \[{{n}^{-\dfrac{1}{3}}}\] in numerator.
So, we have $\dfrac{{{n}^{-\dfrac{1}{3}}}\left( 1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n} \right)}{{{n}^{2}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$
Or, $\dfrac{\sqrt[3]{\dfrac{1}{n}}\left( 1+\sqrt[3]{2}+\sqrt[3]{3}+........+\sqrt[3]{n} \right)}{{{n}^{2}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$
Multiplying, $\sqrt[3]{\dfrac{1}{n}}$ with terms in bracket, we get
$\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{{{n}^{2}}\left( \dfrac{1}{{{(na+1)}^{2}}}+\dfrac{1}{{{(na+2)}^{2}}}+.....+\dfrac{1}{{{(na+n)}^{2}}} \right)}$
Multiplying, $\sqrt[3]{\dfrac{1}{n}}$ with terms in bracket in denominator, we get
$\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{\left( \dfrac{{{n}^{2}}}{{{(na+1)}^{2}}}+\dfrac{{{n}^{2}}}{{{(na+2)}^{2}}}+.....+\dfrac{{{n}^{2}}}{{{(na+n)}^{2}}} \right)}$
Now, in denominator, multiplying denominator and numerator of each terms by $\dfrac{1}{{{n}^{2}}}$, we have
$\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{\left( \dfrac{1}{{{\left( a+\dfrac{1}{n} \right)}^{2}}}+\dfrac{1}{{{\left( a+\dfrac{2}{n} \right)}^{2}}}+.....+\dfrac{1}{{{\left( a+\dfrac{n}{n} \right)}^{2}}} \right)}$
On observing patterns in numerator and denominator, we can write the terms collectively in terms of summation.
So, we can write numerator $\sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}}$ as \[\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}\] and,
Denominator $\dfrac{1}{{{\left( a+\dfrac{1}{n} \right)}^{2}}}+\dfrac{1}{{{\left( a+\dfrac{2}{n} \right)}^{2}}}+.....+\dfrac{1}{{{\left( a+\dfrac{n}{n} \right)}^{2}}}$ as $\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}$.
So, we have whole fraction $\dfrac{\left( \sqrt[3]{\dfrac{1}{n}}+\sqrt[3]{\dfrac{2}{n}}+\sqrt[3]{\dfrac{3}{n}}+........+\sqrt[3]{\dfrac{n}{n}} \right)}{\left( \dfrac{1}{{{\left( a+\dfrac{1}{n} \right)}^{2}}}+\dfrac{1}{{{\left( a+\dfrac{2}{n} \right)}^{2}}}+.....+\dfrac{1}{{{\left( a+\dfrac{n}{n} \right)}^{2}}} \right)}$ as $\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$.
So, $\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$
Now, let $\dfrac{r}{n}=x$
Here r is variable and n is constant
So, differentiating $\dfrac{r}{n}=x$ both side with respect to x, we get
$\dfrac{dr}{n}=dx$
Putting limit in $\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$, we have
$\displaystyle \lim_{n \to \infty}\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$
Now, value of $\dfrac{r}{n}=x$, at r = 1 and $n\to \infty $, we have x = 0 as $\dfrac{1}{\infty }\to 0$ and value of $\dfrac{r}{n}=x$, at r = n and $n\to \infty $, we have x = 1.
So, we can rewrite $\displaystyle \lim_{n \to \infty}\dfrac{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\sqrt[3]{\dfrac{r}{n}}}}{\dfrac{1}{n}\sum\limits_{r=1}^{n}{\dfrac{1}{{{\left( a+\dfrac{r}{n} \right)}^{2}}}}}$ as \[\dfrac{\int\limits_{0}^{1}{\sqrt[3]{x}}dx}{\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}dx}\].
So, let ${{I}_{1}}=\int\limits_{0}^{1}{\sqrt[3]{x}}$ and ${{I}_{2}}=\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}$
We know that \[\int\limits_{a}^{b}{f(x)}=F(b)-F(a)\] and \[\int\limits_{{}}^{{}}{{{x}^{n}}.dx=\dfrac{{{x}^{n+1}}}{n+1}}+C\]
So, ${{I}_{1}}=\int\limits_{0}^{1}{\sqrt[3]{x}}$
${{I}_{1}}=\left( \dfrac{3}{4}{{x}^{\dfrac{4}{3}}} \right)_{0}^{1}$
${{I}_{1}}=\dfrac{3}{4}\left( 1-0 \right)$
So, ${{I}_{1}}=\dfrac{3}{4}$
Now, ${{I}_{2}}=\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}$
Let, a + x = t
At, x = 0, t = a and at x = 1, t = a + 1
Differentiating both sides, we get
dx = dt
so, ${{I}_{2}}=\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}$ is transformed to ${{I}_{2}}=\int\limits_{a}^{a+1}{\dfrac{1}{{{\left( t \right)}^{2}}}}dt$
${{I}_{2}}=\left( -\dfrac{1}{t} \right)_{a}^{a+1}$
${{I}_{2}}=\left( \dfrac{1}{a}-\dfrac{1}{a+1} \right)$
Putting back value of both integral in \[\dfrac{\int\limits_{0}^{1}{\sqrt[3]{x}}dx}{\int\limits_{0}^{1}{\dfrac{1}{{{\left( a+x \right)}^{2}}}}dx}=54\],
We get, \[\dfrac{\dfrac{3}{4}}{\left( \dfrac{1}{a}-\dfrac{1}{a+1} \right)}=54\]
On simplifying, we get
\[\dfrac{1}{72}=\left( \dfrac{1}{a}-\dfrac{1}{a+1} \right)\]
On solving, we get
${{a}^{2}}+a-72=0$
On factorising, we get
${{a}^{2}}+9a-8a-72=0$
On simplifying, we get
( a + 9 )( a – 8 ) = 0
Or, a = -9, 8
So, the correct answers are “Option a and b”.
Note: To solve such a question must know the concept of limit as summation and also, one should not put limit directly as it will give nothing so one must proceed ahead by simplifying the brackets and then use limit as summation to easily simplify the question. Always remember that \[\int\limits_{a}^{b}{f(x)}=F(b)-F(a)\] and \[\int\limits_{{}}^{{}}{{{x}^{n}}.dx=\dfrac{{{x}^{n+1}}}{n+1}}+C\] Try not to make any calculation error as this will make question more complex and hard to solve.
Recently Updated Pages
The real roots of the equation x23 + x13 2 0 are A class 11 maths JEE_Main
Find the reminder when 798 is divided by 5 class 11 maths JEE_Main
Let A and B be two sets containing 2 elements and 4 class 11 maths JEE_Main
A ray of light moving parallel to the xaxis gets reflected class 11 maths JEE_Main
A man on the top of a vertical observation tower o-class-11-maths-JEE_Main
If there are 25 railway stations on a railway line class 11 maths JEE_Main
Trending doubts
JEE Main 2025 Session 2: Application Form (Out), Exam Dates (Released), Eligibility & More
JEE Main Login 2045: Step-by-Step Instructions and Details
JEE Main Chemistry Question Paper with Answer Keys and Solutions
JEE Main Exam Marking Scheme: Detailed Breakdown of Marks and Negative Marking
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
JEE Main Chemistry Exam Pattern 2025
Other Pages
JEE Advanced Marks vs Ranks 2025: Understanding Category-wise Qualifying Marks and Previous Year Cut-offs
NCERT Solutions for Class 11 Maths Chapter 9 Straight Lines
NCERT Solutions for Class 11 Maths Chapter 12 Limits and Derivatives
NCERT Solutions for Class 11 Maths Chapter 8 Sequences and Series
NCERT Solutions for Class 11 Maths Chapter 10 Conic Sections
NCERT Solutions for Class 11 Maths Chapter 13 Statistics